2016
DOI: 10.1097/pra.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Sluggish Cognitive Tempo in a Child and Adolescent Clinical Outpatient Setting

Abstract: Sluggish cognitive tempo (SCT) symptoms have largely emerged from investigations of attention-deficit/hyperactivity disorder (ADHD). Recent research has demonstrated the relevance of SCT symptoms in the field of clinical child and adolescent psychiatry. The goal of this research was to study the symptoms of SCT in a clinical child and adolescent sample and to define its features and comorbid conditions. We reviewed 834 clinical records of patients referred to Child and Adolescent Mental Health Services and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
2
3
0
4
Order By: Relevance
“…Finally, we also found a positive association between dyslexia symptoms and SCT symptoms. These findings are consistent with a previous study that reported a positive association between SCT symptoms and learning disorders (Camprodon-Rosanas et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we also found a positive association between dyslexia symptoms and SCT symptoms. These findings are consistent with a previous study that reported a positive association between SCT symptoms and learning disorders (Camprodon-Rosanas et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…As expected (Barkley, 2013; Camprodon-Rosanas et al, 2016; Carlson & Mann, 2002), among children with elevated SCT, those who also had ADHD were most likely to meet for elevated ADHD based on predominantly IN rather than HI or combined-symptom elevations. Nevertheless, as also found in previous studies (Barkley, 2013; Hinshaw, Carte, Sami, Treuting, & Zupan, 2002; Marshall, Evans, Eiraldi, Becker, & Power, 2014), a subset of children with elevated ratings of SCT met criteria for a co-occurring ADHD-combined presentation.…”
Section: Discussionsupporting
confidence: 70%
“…As expected (Barkley, 2013;Camprodon-Rosanas et al, 2016;Carlson & Mann, 2002), among children with elevated SCT, those who also had ADHD were most likely to meet for elevated ADHD based on predominantly IN rather than HI or combined-symptom This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Independence and Co-occurrence Of Clinically Elevated Sct Ad...mentioning
confidence: 53%
“…In contrast, other work has not shown a consistent association between SCT ratings and child academic performance (Langberg et al, 2014; Marshall et al, 2014), with Bauermeister et al (2012) finding stronger associations between achievement and inattention than between achievement and SCT. A complicating factor may be that children with diagnosed learning disabilities (LD) may be more likely to manifest behaviors associated with SCT symptoms than those without LD diagnoses (Comprodon-Rosanas et al, 2016).…”
mentioning
confidence: 99%